2020
DOI: 10.1002/ajcp.12472
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Structural Barriers to Immigrant Community Participation: The Experience of Peruvians in Santiago de Chile

Abstract: Community participation of immigrants is a pillar for the promotion of social justice. Psychological and structural barriers to community participation of immigrants must be detected. Barriers can be related to historical and transnational connections of immigrants. Barriers can be related to the difficulties of continuing with a community-based organization. Barriers can be related to the psychological empowerment of immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Ten expert dancers are invited to evaluate the innovation and basic features of the robot-imagined dance postures. Each expert is told to evaluate every dance element and score an integer between (Li, 2020 ; Martinez Damia et al, 2021 ) (1—the worst, and 10—the best). When all experts finish scoring, the lowest and highest scores are removed to avoid the negative impact of extreme data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten expert dancers are invited to evaluate the innovation and basic features of the robot-imagined dance postures. Each expert is told to evaluate every dance element and score an integer between (Li, 2020 ; Martinez Damia et al, 2021 ) (1—the worst, and 10—the best). When all experts finish scoring, the lowest and highest scores are removed to avoid the negative impact of extreme data.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 displays the choreographic process by a humanoid robot. “Dance space representation” (Martinez Damia et al, 2021 ) represents all the concepts adopted, including related concepts of joints and limbs on top of the traditional dance-related concepts, such as dance elements and posture. Moreover, the “memory dance space” stores (memorizes) all objects.…”
Section: Methodsmentioning
confidence: 99%
“…Gigliotto et al ( 2022 ) argued that “while collaboration could be fruitful, due to limited resources or administrative challenges there may be tensions arising among groups that struggle for representation in the institutional heritage discourse” (p. 88). Martinez-Damia et al ( 2021 ) also found that competition can be a barrier to attracting new immigrant volunteers, who may not know how to choose which MCBO will best fit their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MCBOs usually provide material (e.g., information, money, legal advice) and immaterial support (e.g., psychological assistance, trustworthy relations, encouragement) to newly arrived migrants who can share concerns and network and fight for their rights in the receiving societies (Aceros et al, 2021 ; Bonnett, 1977 ; Marzana et al, 2020a , 2020b ; Paloma et al, 2010 ). They can also function as settings where immigrants’ cultural identities are protected and differences are negotiated (Martinez-Damia et al, 2021 ; Marzana et al, 2019 ; Sonn, 2002 ; Taurini et al, 2017 ). In line with this, research found that immigrants who participate within community-based organizations are more integrated and have higher psychological well-being compared with those who do not participate (Martinez-Damia et al, 2023 ; Marzana et al, 2020a , 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity for immigrants to have access to spaces where no documentation, money or professional competence are needed is highly relevant. Many community psychologists (Gele & Harsløf, 2012 ; Martinez‐Damia et al, 2021 ; Salami et al, 2019 ) as well as sport researchers (Baker‐Lewton et al, 2016 ; Spaaij, 2013 ; Spaaij et al, 2019 ) have pointed out barriers that immigrants face in their participation. These impediments are especially related to access to structured club‐based sport (transport, lack of resources, policy gaps and competitiveness between organizations) and interpersonal (social disconnection, under‐valued rights, and mistrust), sociocultural (lack of ethno‐cultural diversity and discrimination) and personal constraints (lack of time, health and knowledge regarding the sport system).…”
Section: Discussionmentioning
confidence: 99%